مولانامحمد سرفراز خان صفدرکی تفسیر"ذخیرۃ الجنان" کا منہج و اسلوب: Maulana Muhammad Sarfraz Khan Safdar’s commentary on the style of the collection - Riaz Ahmed Khan; Dr. Muhammad Naseer (Al Manhal Research Journal, 2023)
The correct practical manifestation of the status and rank attained by those fortunate individuals who are associated with the teachings and studies of the Qur'an will only be found in the hereafter. In this successful journey, there was also a fragrance of Sir Syed and the teacher of the Ahl-e-Sunnat, Hazrat Maulana Muhammad Sarfraz Khan Safdar, who along with thousands of people, lit up the torch of Quranic knowledge and understanding and went on this journey with righteousness. May you continue to impart the teachings and spread the guidance of the Quran and wisdom throughout your life. Zakheratul Jinan is the Urdu translation of the Punjabi language Quranic commentary by Maulana Muhammad Sarfraz Khan Safdar. These lectures were delivered in the public after Fajr prayer at the Ghagar Mosque and were subsequently translated from Punjabi to Urdu. To date, 21 volumes of this valuable commentary have been published. The method of teaching this commentary is to first recite a few verses from the Quran, followed by their translation and interpretation, and your approach to teaching this commentary is similar. Often, to explain the relationship and meanings of Quranic chapters, topics, and verses, people refer to the eloquent language of Hazrat Hussain Ali in his book "Bilugat ul Heran Fi Tafsir Ayatul Quran," or the Tafsir al-Kabir of Imam Razi, or the Tafsir Bayan ul Quran of Hazrat Thanwi. These works are cited to provide references and clarify the meanings of Quranic verses and their context. In Quranic exegesis, special emphasis is placed on understanding the specific meanings and contexts of Quranic verses. In addition to relying on the Quran itself, Allah also granted some individuals a special gift and taste in understanding the Quran, which is reflected in their commentary through Quran and Hadith. When interpreting the Quran, the opinions and perspectives of the companions of the Prophet (SAW) are also considered and taken into account.